ANALISIS TINGKAT KEPUASAN PASIEN RAWAT JALAN PESERTA BPJS KESEHATAN TERHADAP PELAYANAN KEFARMASIAN DI INSTALASI FARMASI RUMAH SAKIT EFARINA ETAHAM KOTA PEMATANGSIANTAR TAHUN 2024 - Dilla Sastri Mara; Meyana Marbun, Arsiaty Sumule, Juliana Siboro (Jurnal Kesehatan, 2025)
Quality of service is the level of outpatient satisfaction with pharmaceutical service from a pharmacy installation of Efarina Etaham Hospital Pematangsiantar City isone of the service provided by the health insurance administering agency (BPJS). It is necessary to obtain input on the extent of patiemt satisfaction with the service provided, especially in the pharmaceutical service section. This research is a descriptive analityc study with purposive sampling method, the research starts from the collection of data 02 july to 03 august 2024 to report the results of the research. The study was conducted everyday with a sample of 80 people and used a questionnaire as a measurement tool in which respondents were asked too fill out the questionnaire were outpatients BPJS health participants. The data that has been collected is analyzed descriptively using SPSS software that is addressed through the parameters of the level of satisfaction that is reliability, responsibility, assurance, empathy, and tangible.The level outpatient satisfaction of BPJS health in pharmacy outpatient with pharmaceutical services at Efarina Etaham Hospital, Pematangsiantar city, was obtained by the percentage of reliability 90,46% (very satisfied), responsiviness 98,16% (very satisfied), assurance 93,95% (very satisfied), empathy 99,79% (very satisfied), anf tangilible 104,49% (very satisfied), with an average satisfaction level of 97,33% and include in the very satisfied category. Statistical test of respondent characteristics such as gender, education, occupatient, patient age did not age affect the level of satisfaction of outpatients BPJS health participants to pharmacy services at the pharmacy installation of Efarina Etaham Hospital Pematangsiantar City